Analysis of the Level of Sport Infrastructure on a Local and Regional Basis - Mamcarczyk, Mariola (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The article presents a method allowing a comparative analysis of the level of sport infrastructure in a cross-section of territorial units (voivodeships of Poland, and Wadowice, the county seat). Knowing the number of sports facilities in relation to the number of inhabitants enables communities to establish a policy for developing local sports infrastructure. Due to the availability of data, the analysis was possible only for the years 2010 and 2014. The data on sports facilities were provided by the Provincial Statistical Office in Krakow. The number of inhabitants per sports facility in all territorial units was examined.